(untitled) (The Gaze: Journal of Tourism and Hospitality, 2016)
As a result of highly impressive socio-behavioral temperament and character of the Sherpas in the eastern mountains, many people may be influenced to visit Nepal again and again and the outcome could be the spread of global brotherhood of the Nepalese people. The Sherpas are regarded as the symbolic source of inspiration by means of their simplicity of living, grounded religious and spiritual faith and trustworthiness - all contributing in an experiential living in the Himalayas. This article presents with an exploration of the problems, challenges and prospects for promoting sustainable mountain tourism keeping the Hilarity of the Sherpa Spirit at the center of concern while establishing a world view on sustainable tourism development and supplementing it with the grounded multiple realities via ethnographic dialectics. The Gaze: Journal of Tourism and Hospitality Vol.6 2014 pp.42-69